2017
DOI: 10.1177/1540796917698831
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Instructional Methods to Teach Employment Skills to Secondary Students With Intellectual and Developmental Disabilities

Abstract: Effective vocational instruction is an essential aspect of preparing students with intellectual and developmental disabilities (IDD) for the world of work. We systematically reviewed research on instructional methods used to teach employment skills to secondary students with IDD. We identified 56 studies involving 766 participants with IDD. Four intervention approaches emphasized technology or some other instructional stimulus (i.e., self-management devices, video-based, audio-based, picture and tactile-based)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 50 publications
4
62
0
1
Order By: Relevance
“…Elements of the training's approach, that is, tailoring to the individual, involving the support network and assisting the transfer of learnt skills to daily life, seem to benefit people with intellectual disabilities. This has already been suggested in previous research (Cavkaytar et al., ; Douglas et al., ; Gilson et al., ; Goldschmidt & Song, ; Hale et al., ; Kuijken et al., ; Young et al., ); however, our study for the first time evaluated a self‐management training in which all these elements were combined and which showed that this is a promising approach.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Elements of the training's approach, that is, tailoring to the individual, involving the support network and assisting the transfer of learnt skills to daily life, seem to benefit people with intellectual disabilities. This has already been suggested in previous research (Cavkaytar et al., ; Douglas et al., ; Gilson et al., ; Goldschmidt & Song, ; Hale et al., ; Kuijken et al., ; Young et al., ); however, our study for the first time evaluated a self‐management training in which all these elements were combined and which showed that this is a promising approach.…”
Section: Discussionsupporting
confidence: 67%
“…To our best knowledge, none of the investigated interventions were generalized to a wider range of people with intellectual disabilities with different self‐management goals. Previous research focused, for example, on prompting (Bouck, Satsangi, & Bartlett, ; Dollar et al., ; Wu, Wheaton, & Cannella‐Malone, ), the use of technology (Cannella‐Malone et al., ; Cavkaytar, Acungil, & Tomris, ; Cullen, Alber‐Morgan, Simmons‐Reed, & Izzo, ; Douglas, Ayres, & Langone, ; Ramdoss et al., ), employment (Gilson, Carter, & Biggs, ; Gomes‐Machado, Santos, Schoen, & Chiari, ) or health behaviour (Taggart et al., ; Wilson & Goodman, ). Most studies presented promising results, but drawing firm conclusions about the effects of self‐management interventions is difficult due to studies’ narrow focus and methodological limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autistic students have described myriad barriers prior to starting their doctorate. Disabled learners often follow non-traditional paths through education, leading to CVs with gaps around traditional entry qualifications and work experience (Barnham, 2016;Brede et al, 2017;Douglas et al, 2016;Gilson et al, 2017, Sproston et al, 2017Young-Southward et al, 2017). One respondent described school having knocked their confidence.…”
Section: Emerging Themesmentioning
confidence: 99%
“…Single-case research designs incorporate experimental methodology originating from experimental and applied behaviour analysis, 1−3 and have played a pivotal role over the last several decades in the development of evidence-based practices for individuals with and at risk for neurodevelopmental disability and behavioural disorders. [4][5][6] Extensive meta-analyses and systematic literature reviews of single-case research have synthesized the effectiveness of intervention practices for children and youth with intellectual and developmental disabilities, [7][8][9] and children and youth with behavioural or academic concerns 10,11 as well as across a wide variety of other disabilities or at risk populations, intervention type, adaptive behaviour domains, and settings. Importantly, single-case research designs have provided researchers with a rigorous experimental alternative to nonexperimental AB case series.…”
Section: Special Issue On Advances In Single-case Research Design Andmentioning
confidence: 99%